Identification and analysis of bacterial presence in diagnostic imaging equipment (Research, Society and Development, 2020)
The objective of this research was to analyze the bacterial presence in diagnostic imaging equipment, which in day-to-day hospital life are often used for disease diagnosis. Samples were collected from three diagnostic equipment, using the swab technique, for laboratory sowing and subsequent identification. According to the laboratory analyses, the presence of some types of bacteria was proven, which depending on how the patient's immune system is, can be harmful to the human organism, besides yeast and fungus colonies in large quantities were observed in some compartments of the collected apparatuses, other constituents of the collected apparatuses were not possible to identify any type of bacteria, fungus or yeast colony. The importance of bacterial analyses in imaging diagnostic devices is visible, since they can harbor dangerous types of bacteria or fungi and this can end up causing infections in patients who use the equipment in question.